Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/hed.25634
|View full text |Cite
|
Sign up to set email alerts
|

Unique mutation patterns in anaplastic thyroid cancer identified by comprehensive genomic profiling

Abstract: Introduction Anaplastic thyroid cancer (ATC) is a highly aggressive thyroid cancer. Those ATC with genomic alterations (GAs) in TSC2, ALK, and BRAF may respond to targeted therapies. Methods Comprehensive genomic profiling on 90 ATC specimens identified base substitutions, short insertions and deletions, amplifications, copy number alterations, and genomic rearrangements in up to 315 cancer‐related genes and 28 genes commonly rearranged in cancer. Results Median patient age was 65 (range, 33‐86) years, 50 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…RAS mutation rate in ATC was reported ranging from 18% to 44.4%. In our cohort, N-RAS mutation was the most frequent (eight cases, 29.6%) among the three RAS subtypes, concordant with findings in previous reports [9,13,15,16]. K-RAS mutation was present in three cases (11.1%), while H-RAS mutation was not detected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…RAS mutation rate in ATC was reported ranging from 18% to 44.4%. In our cohort, N-RAS mutation was the most frequent (eight cases, 29.6%) among the three RAS subtypes, concordant with findings in previous reports [9,13,15,16]. K-RAS mutation was present in three cases (11.1%), while H-RAS mutation was not detected.…”
Section: Discussionsupporting
confidence: 92%
“…The BRAF-driven PTC has lower expression of thyroid differentiation genes, a higher risk of tumor recurrence, and strong MAP kinase signaling activation as opposed to activation of both MAP kinase and PI3 kinase pathways in RAS-driven PTC [7]. RAS and BRAF V600E mutations were also commonly mutated genes in ATC [8][9][10][11][12][13][14][15][16][17]. Studies indicated that RAS-driven and BRAF-driven ATC share homogenous transcriptome with an undifferentiated thyroid gene expression profile [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with prior literature. [4][5][6][7][8][9][10][11][12][13] In the referenced studies, the overall BRAF V600E mutation rate is 30%, although the mutation rate varies widely between studies. This wide range may, in part, reflect differences in cohort characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher BRAF V600E mutation rate in ATC has been found to be associated with older patient age. 7,12 Additionally, the BRAF V600E mutation rate could be due to differences in genetic background or iodine intake. The highest reported BRAF V600E mutation rate in ATC is 91% and was reported in a cohort in Korea, 6 where the prevalence of the BRAF V600E mutation in PTC is higher than it is in other geographical regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation